Condition monitoring of electric motor - Ngadiron, Zuraidah (2007)
Condition monitoring on electric motor is a preventive maintenance in order to avoid problems and hazard from happening to the machinery, also to prevent personal injury with the major factor is insulation resistance. In this thesis, to further discuss this issue, the developed experiment with the measuring technique of the condition of electric motor on insulation resistance is used. Then, the experiment rig was developed applied to Thrige Odense Denmark 3-phase induction motor for case stud} to obserxe the condition monitoring on insulation resistance. The validity of the data was then taken using the megohmmeter and temperature indicator. The experiment is to monitor the Denmark manufactured motor condition of insulation whether is good. fair, poor or bad by following the IEEE standard procedure. This prexentixe maintenance test can be done on a monthlx. semiannual or annual basis as conditions demand. The data from the test is plotted to graph to get the trended data of the insulation. The theoretical and experiment studies include the effect of the humiditx and temperature to the insulation. Tests rig for the experimental work are developed using IEEE Standard 43-2000. IEEE Recommended Practice for Testing Insulation Resistance of Rotating Machinery and A Guide To Diagnostic Insulation Testing Above lkV by Megger Ltd. Second Edition 2002. The results have been compared to the standard and analyses are presented in graph. From the developed procedure and methods prove that the temperature affects the insulation winding at 3-phase induction motor (2 speed : 2 winding). For case study, the motor has been soaked for three days to apply flooded condition. The result shows that the motor insulation condition is even better after comparison with the standard manufactured data at 821 MH and 893 MH change to more than 999 Mfi for both winding condition after drying out experiment.